Optimization and Formulation of Fenofibrate Transfersome Using The Thin Layer Hydration Method - Putri, Sukma Oktafiani; Iswandi, Iswandi; Kuncahyo, Ilham (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Abstract Background: Fenofibrate is a lipophilic drug that is used to treat hypercholesterolemia and hypertriglyceridemia in patients.. The low solubility of fenofibrate can be improved by creating a phenofibrate transfersome delivery system. The objective of this research was to determine the effect of phosphatidylcholine 90G, Tween 80, with sonication on fenofibrate transfersomesand to obtain the optimum composition of phosphatidylcholine 90G, tween 80, with sonication on critical parameters including particle size, zeta potential, absorption efficiency. For formula optimization, the factorial design method was applied. Phosphatidylcholine 90G composition, tween 80, with sonication were used as independent variables, with particle size, zeta potential, and sorption effectiveness as dependent variables. Method: The optimization was carried out with critical parameters of the fenofibrate transfersomes tested including particle size, zeta potential, and adsorption efficiency. The critical parameter test data were analyzed using factorial design. Result: The results showed that there was an effect of phosphatidylcholine 90G, tween 80, and sonication on fenofibrate transfersomes provide effect by including particle size, zeta potential, and sorption efficiency. Conclusion: The optimum proportion of phosphatidylcholine 90G was 95%, tween 80 was 5%, and sonication was 33,39 time. The transfersome ability of fenofibrate was good in the optimum formula in the particle size test was 23,675 nm and zeta potential 52,231 mv and the entrapment efficiency was 96,915 %. Keyword : Fenofibrat, Transfersome, phospatidicoline 90G, thin film layer, Factorial Design.